Occult Breast Carcinoma Is More Common in Women Undergoing Breast Reduction after Contralateral Cancer: A Systematic Review and Meta-Analysis. Issue 2 (August 2020) - Fitzpatrick, Siobhan E.; Lam, Thomas C.
Abstract : Background: Occult breast carcinoma is occasionally found in breast reduction specimens. Although its incidence varies widely, there is a trend toward an increased incidence for women with a history of breast cancer. The authors performed a systematic review and meta-analysis of occult carcinoma incidence in breast reduction specimens. Methods: The MEDLINE and Embase databases were searched for peer-reviewed studies with no language restrictions for studies that recorded the incidence of occult carcinoma in breast reduction specimens. Cancer incidence per specimen was pooled for women with and without a history of breast cancer. Results: Forty-two studies were eligible for inclusion, of which 29 were quantitatively analyzed. The pooled incidence of carcinoma was higher within specimens from women with breast cancer (3.4 percent; 95 percent CI, 2.2 to 5.3 percent) than without (0.6 percent; 95 percent CI, 0.4 to 0.8 percent), and this increased likelihood was significant when populations were compared directly (OR, 6.02; 95 percent CI, 3.06 to 11.86; p < 0.0001). Conclusions: Women with a history of breast cancer have an increased incidence of occult breast carcinoma within their breast reduction specimens compared with women with no breast cancer history. There is a need for preoperative radiology screening, counseling, and histopathology guidelines to ensure adequate diagnosis and management of these women.